FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN - Siti Indar Masfiroh; Ignes Januar Cahyadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about what effect of manaerial ownership, independence commissioners, audit committee, firm size, profitability, liquidity, leverage and free cash flow. This research uses 59 non-financial companies listed in Indonesia Stock Exchange selected using purposive sampling method during the period 2014 to 2016. The data of this research were analyzed using multiple linear regression analysis method in the research model. The results of this research indicate that the profitability, leverage and free cash flow affect the value of the company. While managerial ownership, independent commissioners, audit committee, firm size, and liquidity have no effect on company value.